Cryostratigraphy and ground-ice content of the upper permafrost in Alaska, 2018-2023 - Mikhail Kanevskiy; Yuri Shur; Benjamin Jones; M Torre Jorgenson (Arctic Data Center, 2023)
This dataset contains information on cryostratigraphy and ground-ice content of the upper permafrost, which was based on the results of 2018-2023 field work in various regions of Alaska and Canadian Arctic including the following study areas: Utqiagvik (former Barrow), Teshekpuk Lake, Prudhoe Bay Oilfield, Toolik Lake, Jago River, Itkillik River, Anaktuvuk River, Fairbanks, Dalton Highway, Glennallen, Point Lay, Bylot Island (Canada), Inuvik-Tuktoyaktuk (Canada). Cryostratigraphy of the upper permafrost was studied mainly in coastal and riverbank exposures and frozen cores obtained from drilling with the SIPRE corer. Permafrost exposures and cores were described and photographed in the field, and obtained soil samples were delivered to the University of Alaska Fairbanks for additional descriptions and analyses. Ice contents of frozen soils (including gravimetric and volumetric moisture content, excess-ice content) were measured. The dataset includes cryostratigraphic descriptions, gravimetric (GMC) and volumetric (VMC) moisture content, excess-ice content (EIC), electrical conductivity (EC) and photographs of the permafrost exposures and frozen cores obtained from boreholes.